Determinação do efeito magnetocalórico dos intermetálicos Nd2(Rh,Ir)In8, Nd2Ni2In e Dy2RhGa8 e ajuste da transição metamegnética da serie RRhIn5 (R: Nd,Tb,Dy e Ho) - Santos, José Anselmo da Silva (2021)
In this thesis we study the magnetocaloric effect - (MCE) and metamagnetic transitions of intermetallic at based on rare earths with an effective Hamiltonian model that contemplates the interactions of: crystalline electric field - (CEF), Zeeman and exchange (in the approximation of molecular field) applied to two and four subnets and quadrupolar interaction when necessary. We developed a computational program that simulates and adjusts experimental magnetization data by the Newton-Search method to determine the magnetic properties, such as: magnetization, internal energy and specific heat. In addition, we elaborate a system in C# language to calculate the magnetocaloric effect via magnetization curves, both M×T and M×H, from specific heat curves and directly from entropy curves. In our computational program we implemented the interactions of CEF, quadrupolar and magnetic applied to two and four subnets and tested the model in data adjusts of the magnetization and magnetocaloric in five monocrystalline intermetallic systems: Nd2(Rh, Ir)In8 with tetragonal structure and antiferromagnetic order, we adjust magnetization curves M×H, M×T, dS×T and suggest new parameters of CEF and exchange, Nd2Ni8In tetragonal e ferromagnético na direção [001], ajustamos curvas de magnetização e de MCE e o Dy2RhGa8, which is antiferromagnetic and tetragonal, we determine the parameters of quadrupolar, CEF and exchange interactions, we adjust M×T, M×H and dS×T curves in the two main crystallographic directions and finally we adjust the metamagnetic transitions in the serie of RRhIn5 compounds (Nd, Tb, Dy, Ho) with the model of four subnets.